Academic Training in Oral and Maxillofacial Surgery – when and how to enter the pathway. Issue 2 (February 2023) - Payne, Karl F.B.; Higginson, James; Basyuni, Shadi; Goodson, Alexander M.C.; Chadha, Ambika; Elledge, Ross; Breeze, John; Goodson, Michaela; Bajwa, Mandeep S.; Schilling, Clare; Shaw, Richard J.; Fan, Kathleen; et al.
Abstract: Entering into surgical academia can seem a daunting prospect for an oral and maxillofacial surgery (OMFS) trainee. However, the streamlining of academic training by the NIHR to create the integrated academic training (IAT) pathway has simplified academic training and more clearly defined academic positions and entry points for trainees. In this article we review the current NIHR IAT pathway and the various grades and entry points available to OMF surgeons, both pre- and post-doctoral. We highlight the unique challenges facing OMF trainees and provide advice and insight from both junior and senior OMFS academics. Finally, we focus on the planning and application for a doctoral research fellowship – discussing funding streams available to OMF surgeons.